Central Retinal Vein Occlusion Associated with Ulcerative Colitis. Issue 12 (December 2016) - Seo, Yuri; Kim, Min; Kim, Jin Hyoung; Park, Jae Jun; Lee, Sung Chul
ABSTRACT: Purpose: To report a case of central retinal vein occlusion without macular edema associated with ulcerative colitis and its novel treatment with intravitreal dexamethasone. Case Report: A 40-year-old man with ulcerative colitis presented with sudden visual disturbances. An initial fundus examination showed subtle yellow-to-white patches within the inner retina of the right eye superotemporal to the fovea. There were intraretinal hemorrhages and cotton-wool spots within the superior vascular arcade and nasal to the optic disc. Despite initiation of systemic corticosteroids, 2 weeks later there was an increase in retinal hemorrhages, formation of cotton wool spots, and development of optic disc swelling in the right eye. The patient was eventually diagnosed with nonischemic central retinal vein occlusion associated with ulcerative colitis. He received sustained-release intravitreal dexamethasone, which led to the resolution of retinal hemorrhage, optic disc swelling, and cotton-wool spots. Three months after the injection, retinal hemorrhages were not detectable. However, ocular coherence imaging showed marked thinning of the inner retina at the locations that were previously hyper-reflective. Conclusions: Central retinal vein occlusion is an uncommon ophthalmologic manifestation associated with ulcerative colitis. Injection of intravitreal dexamethasone could be a viable treatment option in these patients even without the presence of macular edema.